Analisis Efisiensi dan Efektivitas Keuangan Berdasarkan Analisis Rasio pada PT Eastparc Hotel Tbk - Benjiro Stevano Lepar; Brandon Gregorius Fandra; Darren Owen Cornelius; Dyah Cahyasari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Financial statements are an essential part of a company for conducting its operational activities. There are several reasons why these financial statements are important to prepare. One reason is to obtain information for assessing the performance of a company. Financial statements typically employ ratio analysis, such as Liquidity Ratios, Solvency Ratios, Activity Ratios, and Profitability Ratios. This ratio analysis provides a clearer picture of the company's financial position and its ability to meet short-term and long-term obligations. This journal contains calculations regarding the financial statements of PT Eastparc Hotel Tbk using ratio analysis from 2020 to 2023. The analysis indicates that PT Eastparc Hotel Tbk exhibits financial conditions that require improvement in several areas, particularly in terms of liquidity, which has not fully met industry standards. Other aspects also need to be addressed, as these ratios reflect the overall performance of the company and can potentially influence management and investor decisions in the long term.